COPD is a risk factor for COVID-19, but does not confer increased severity of the disease. (November 2021) - Jeong, Jae Seok; Kim, Jong Seung; You, Yeon Seok; Yeom, Sang Woo; Lee, Yong Chul
Abstract: Epidemiologic studies suggest that COPD is associated with an increased risk of poor outcome in patients with COVID-19, although they failed to demonstrate COPD as a risk factor for acquiring COVID-19. However, most data have come from a limited global population. In this nationwide cohort study based on the Korean national health insurance claims-based database, COPD is associated with increased risk for COVID-19 and having COPD does not seem to confer substantial risk for severe COVID-19 and mortality. These findings indicate that heterogeneity in the populations across many countries may complicate the net effects of COPD on the COVID-19-related outcomes.